Estudo da resposta de tecidos de Citrus sinensis em fases ontogenéticas distintas à infecção por Candidatus Liberibacter asiaticus - Silva, Mayara Gobetti Fernandes da (2021)
The objective was to develop analytical methods to evaluate the variation in the chemical profile between specimens of juvenile and mature tissues of Pera orange (C. sinensis) in cuttings and grafted on Rangpur lime (C. limonia) with symptoms of HLB, and without the bacteria, aiming to understand the resistance of the juvenile plants in relation to the mature tissue in the cuttings and in the graft. The seedlings were prepared from seed and these later provided cuttings which were rooted. The mature seedlings were obtained from segments of Pera orange seedlings produced in graft with Rangpur lime, and yielded cuttings, which were rooted. After 30 days in the humid chamber, the rooted cuttings were transplanted to pots where they remained for 6 months. The grafts were obtained by removing buds from the healthy juvenile and mature orange pear plants obtained as above. The grafted plants were 6-month-old Rangpur lemon seedlings, also healthy. Bubbles were removed from symptomatic Pera orange plants (with Ca. L. asiaticus) and grafted onto the healthy plants mentioned above. After inoculation of the bacteria by bubbles, the plants were evaluated by PCR at 10, 30, 60 and 120 days. After 120 days, mature plants showed positive PCR for root, lower stem, upper stem and leaves, while juveniles also had the same responses, however, their leaves, PCR indicated absence of the bacteria. The study of the chemical profile was carried out with the plants after 120 days of inoculation with the bacteria. These plants were collected and separated into root, lower stem, upper stem and leaves, dried and crushed. This dry material was stored in a freezer at -80 oC. These dry materials were extracted with MeOH:H2O (1:1) and analyzed by UPLC-QToF/MS individually. The data obtained were compared by means of multivariate analysis by PCA and OPLS-DA/S-Plot, and these indicated the fractions to be studied, that is, those where there was a variation in the chemical profile in the presence of the bacteria. An analytical method using UPLC-QToF/MS was developed to identify the main compounds and determine their relative amounts in all fractions suggested by the multivariate analysis. Studies have shown that coumarins are always present in greater concentration in mature tissues, and are present in the lower parts of the graft. Only one coumarin was detected in the upper stem and leaves, 7-demethylisotamarin, and also with the highest concentration in mature tissues. Only two flavonoids were detected at the base of the graft (lower stem), nobiletin and tangeretin. In the other upper parts, several other flavonoids were detected, and all in greater concentration in the juvenile tissues. An analytical method using HPLC-UV was developed to quantify the coumarins xanthylethine, seseline and 5-methoxyseseline, and the flavonoid hesperidin. This study confirmed seselin with a high increase in the presence of the bacteria, while the flavonoid hesperidin had its concentration drastically reduced in the presence of the bacteria. The data suggest energy savings, and this being channeled into the biosynthesis of more coumarins. Coumarins are present in the lower parts of the graft and must have bactericidal potential against Ca. Liberibacter asiaticus, whose initial development occurs in the roots.